The Rejection of Domination and Submissiveness in the Qur'an the Verses of 279 Surah al-Bagharah, 141 al-Nisa, 83 al-Ghasas - Aziz Khaleghi Baigi; Mostafa Rajaeipour; Hossein Ahmari (آموزه‌های قرآنی, 2019)
The concept of domination has mentioned with various terms and expressions in the Holy Qur'an such as cruelty, rebellion, greed, path, transgression, arrogance, eminence. And the rejection of domination and disapproval of submissiveness and their verdicts are the contents of many verses in the Qur'an which in this regard, the implication of the verses 279 al-Baqarah, 141 al-Nisa and 83 al-Qasas are surveyed comparatively. And the consequences, the adverse effects of domination, way of liberation from domineering and anti-arrogance methods will be pointed. The study shows that the scope of the last passage of verse 279 of Baqarah (you do no wrong, nor are you wronged) in relation to these concepts is much broader than other verses and even the verse “negation of path” but the establishment of a rule called “the rule of negation of injustice” for the necessary citations and uses In this case, has been neglected, and this paper first of all attempts to explain this important point. The purpose is to make greater use of the Qur'anic guidelines and teachings and to make Muslims aware of the ominous effects and deceptions of world-dominated systems and effective methods of anti-arrogance especially for foreign policy-makers and mediators. This essay utilizes the inspirations of the Holy Qur'an and the guidance of those who are firmly rooted in knowledge, the Ahlul-Bayt (pbuh) and the views of some commentators and interpreters of the verses of verdicts (Ayat-ol-Ahkam) in jurisprudential, legal and political fields, explain and approach the above issues with analytical and descriptive insights as far as possible.